2008
DOI: 10.3961/jpmph.2008.41.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Intra-Individual Variation of Urinary Malondialdehyde and 2-Naphthol

Abstract: These results suggest that urinary MDA and 2-naphthol remain stable under variable storage conditions, even at room temperature for 16 hours, and indicate that these markers can be used in epidemiological studies involving various sample storage conditions. The intra-CC of urinary 2-naphthol and MDA were acceptable for application to epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…MDA standards (0.1, 0.5, 1, 2, and 4μmol/L) were prepared with 1,1,3,3-tetramethoxypropane. The LOD was 0.05μmol/L, the correlation for the linearity of the standard curve was0.99 and the CV was less than 10% (20). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDA standards (0.1, 0.5, 1, 2, and 4μmol/L) were prepared with 1,1,3,3-tetramethoxypropane. The LOD was 0.05μmol/L, the correlation for the linearity of the standard curve was0.99 and the CV was less than 10% (20). …”
Section: Methodsmentioning
confidence: 99%
“…Excitation/emission wavelengths used in the detection of 2-naphthol was 227/355 nm. The LOD was 0.5ng/ml and the CV was less than 15% (20). …”
Section: Methodsmentioning
confidence: 99%
“…Lee and Kang [20] n = 10 -2.43 ± 0.19 HPLC-FL Lee and Kang [20] n = 44 -1.52 ± 0.20 HPLC-FL Kil et al [21] n = 500 0.01 -11.86 2.15 ± 1.60 HPLC-FL studies performed with HPLC separation of MDA-TBA2 adduct. Furthermore, it is demonstrated that MDA is stabile in urine at room temperature for 24 h and when stored at -20 °C for 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al [22] observed that MDA is unstable when stored at -20 °C for longer than three weeks, with an observed increase of MDA level in plasma stored for 1 month to 1 year. Lee and Kang [20] showed that MDA is stable in urine at room temperature and at -20 °C for 16 hours. In this study, the stability of MDA in urine was assessed at room temperature for 24 h and when stored at -20 °C for 6 months.…”
Section: Stability Of Mda In Urine Samplesmentioning
confidence: 99%
See 1 more Smart Citation